Uji Efektivitas Daun Beluntas (Pluchea indica Less) Untuk Mengurangi Keputihan Dari Jamur Candida albicans Pada Remaja - Bina Marsasi; Julia, Dina; Dalinur Qur'andini; Magumi, Novita (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2025)
Beluntas leaves are useful for treating vaginal discharge caused by fungi, therefore they have antifungal properties. This study aimed to determine the antifungal activity of beluntas leaf extract (Pluchea indica Lees) against Candida albicans in adolescents. The purpose of this study was to determine the effect of using a decoction of beluntas leaves on vaginal discharge in adolescents. This study used a quantitative, pre-experimental research method with a one-group pretest-posttest design. Based on the statistical results using the Mann-Whitney U-Test, a p-value of 0.000 <0.05 was obtained, indicating a difference in the duration of vaginal discharge reduction between respondents who consumed the decoction of beluntas leaves and those who did not. It can be concluded that the use of decoction of beluntas leaves does have an effect on vaginal discharge in adolescents.